Inflammatory checkpoints in amyotrophic lateral sclerosis: From biomarkers to therapeutic targets - Jiang, Zongzhi; Wang, Ziyi; Wei, Xiaojing; Yu, Xue-Fan (Frontiers in Immunology, 2022)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by progressive motor neuron damage. Due to the complexity of the ALS, so far the etiology and underlying pathogenesis of sporadic ALS are not completely understood. Recently, many studies have emphasized the role of inflammatory networks, which are comprised of various inflammatory molecules and proteins in the pathogenesis of ALS. Inflammatory molecules and proteins may be used as independent predictors of patient survival and might be used in patient stratification and in evaluating the therapeutic response in clinical trials. This review article describes the latest advances in various inflammatory markers in ALS and its animal models. In particular, this review discusses the role of inflammatory molecule markers in the pathogenesis of the disease and their relationship with clinical parameters. We also highlight the advantages and disadvantages of applying inflammatory markers in clinical manifestations, animal studies, and drug clinical trials. Further, we summarize the potential application of some inflammatory biomarkers as new therapeutic targets and therapeutic strategies, which would perhaps expand the therapeutic interventions for ALS.